Effect of systemically applied octreotide on serum oxidanvanti-oxidant parameters and lipid peroxidation in piristane-induced arthritis - Ardicoglu, O; Ozgocmen, S; Pekkutucu, I; Ozyurt, H; Sogut, S; Kamanli, A (Bmj Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL